Lipoprotein(a) in Personalized Cardiovascular Prevention: Risk Stratification, Coronary Artery Calcium, and Emerging Lp(a)-Lowering Therapies - Alveena Batool Syed; Samuel Michalak; Indra Kiran Reddy Potulapati; Aravinthan Vignarajah; Gautam V. Shah (Journal of Clinical Medicine, 2026)
Lipoprotein(a) [Lp(a)] is an independent and causal risk factor for atherosclerotic cardiovascular disease (ASCVD) and calcific aortic valve stenosis (CAVS), with plasma levels largely genetically determined and minimally influenced by lifestyle. Contemporary dyslipidemia guidelines now recommend at least one lifetime measurement and increasingly incorporate Lp(a) into personalized cardiovascular risk evaluation. Recent guideline updates integrate traditional risk estimation with risk-enhancing factors and coronary artery calcium (CAC) imaging. The 2026 U.S. multi-society guideline classifies Lp(a) ≥ 125 nmol/L as a risk-enhancing factor and ≥250 nmol/L as a major risk enhancer. The PREVENT equations provide baseline risk estimation, personalized by Lp(a) and refined through CAC-based reclassification when treatment decisions remain uncertain. Despite its established role in risk assessment, current management remains indirect and emphasizes aggressive control of modifiable risk factors, particularly low-density lipoprotein cholesterol (LDL-C). Emerging Lp(a)-targeted therapies, including antisense oligonucleotides, small interfering RNA agents, and oral small-molecule inhibitors, have shown substantial and sustained reductions in Lp(a) levels, although definitive evidence of cardiovascular benefit is still pending. This review provides a practical, evidence-based synthesis of Lp(a) biology, contemporary guideline recommendations, integrated risk stratification using PREVENT and CAC, current management, and emerging Lp(a)-targeted therapies for use across primary care and cardiology practice.